Relationships between physical activity, fundamental motor skills, and body mass index in preschool children - Ma, Fei-Fei; Luo, Dong-Mei (Frontiers in Public Health, 2023)
Purpose: To investigate whether there is a potential relationship between physical activity (PA), fundamental motor skills (FMS), and Body Mass Index (BMI) in preschool children and to further explore the differences in PA and FMS between normal weight and overweight/obese preschool children. Method: Participants were 366 preschool children aged 3 to 6 years; 358 completed all tests (194 boys and 164 girls). PA, FMS, body weight, and height were measured by triaxial accelerometer, the Test of Gross Motor Development, Second Edition (TGMD-2), and anthropometry measurement, respectively. Result: The overall rate of overweight/obesity was 17.0%, with no significant gender difference (χ2=0.628, p=0.428). Older children perform significantly better in both object control skills and locomotor skills. Independent samples t-tests were used to examine the difference between genders on FMS and PA: girls in the 5-year-old group display better locomotor skills (p=0.012) than boys. Boys spent more time on moderate to vigorous physical activity (MVPA) and less time on sedentary activity when compared to girls. Results of partial correlation analysis showed that PA was significantly and positively correlated with both locomotor skills and object control skills in preschool children (p < 0.01), while there was no correlation between FMS, PA level, and BMI. Results of ANCOVA revealed no significant difference in FMS between normal-weight and overweight or obese preschool children; normal-weight girls had significantly longer MPA and MVPA duration and significantly shorter sedentary periods than overweight or obese girls (p < 0.05). Conclusion: Overweight/obesity in preschool children requires effective measures. PA is positively associated with FMS, while BMI is not potentially related to FMS or PA in preschool years. Overweight or obese girls should develop healthier weight status by increasing MVPA hours and reducing sedentary time.